From smallpox to COVID-19: epidemics and caricatures in the history of Peru: About the book Children of the Plague by Marcel Velázquez Castro - Tauzin-Castellanos, Isabelle (2021)
Children of the plague (Lima: Taurus, 2020, 246 pp.) is a book of essays published by the Peruvian literary critic Marcel Velázquez Castro in October 2020 based on the experience of COVID-19 and the history of epidemics in Peru. Enjoyable reading —that is, without the boredom that often appears in books saturated with notes—, Children of the Plague is distinguished, on the contrary, by the flexibility of thought, the argumentative ability and the humanism in solidarity with the victims of the pandemic. , while attacking Peru's endemic evils intensified by COVID: hegemonic arrogance, corruption and racism in public life. Children of the Plague is a brave book, in which Velázquez Castro demonstrates singular insight by resorting to a tool that he has known thoroughly since 2008, when he organized congresses on the history of the Peruvian press: in this year 2020 he recovers the visual discourse of cartoons of the graphic press of the beginning of the 20th century (Variedades, Monos y Monadas, Fray K. Bezón), as well as the medical-hygienist advertising of a century ago.